2015
DOI: 10.1017/s1041610215001714
|View full text |Cite
|
Sign up to set email alerts
|

Empowerment of young people who have a parent living with dementia: a social model perspective

Abstract: Background:Socially constructed disablement has marginalized young people in families where a parent has younger onset dementia (YOD). This has contributed to inadequate societal support for their complex situation. Impacts on such young people include significant involvement with mental health services for themselves. In this paper, we explored the young people's lived experiences in these families and the influencing factors to enable these young people to be included and supported within their community.Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(55 citation statements)
references
References 48 publications
1
53
0
1
Order By: Relevance
“…Their support needs differ considerably from those of people with dementia in later years (AM Beattie, Daker-White, Gilliard, & Means, 2002;Sansoni et al, 2016;Sansoni et al, 2014;Thompson, 2011;Tyson, 2007;Westera et al, 2014) as they still have comparatively high levels of physical fitness and are not wellmatched to join more sedentary services designed for older age groups (Pamela Roach, Drummond, & Keady, 2016;Tolhurst, Bhattacharyya, & Kingston, 2014). They also need to negotiate changing family dynamics with a particular focus on children and teenagers (Chow, Pio, & Rockwood, 2011;Gibson, Anderson, & Acocks, 2014;Hutchinson, Roberts, Daly, Bulsara, & Kurrle, 2016;Johannessen, Bruvik, & Hauge, 2015;Lockeridge & Simpson, 2013;Morhardt et al, 2015;P. Roach & Drummond, 2014;Shnall, 2015;Svanberg, Spector, & Stott, 2011;Thompson, 2011), accommodate changing care needs along the disease trajectory (Bakker et al, 2013;Bakker et al, 2010) and need to seek financial and legal advice as employment is discontinued and spouses give up work to become the main caregiver or take on work to compensate for lost income (Alzheimer's Society, 2015;Chaplin & Davidson, 2016;Picard, Pasquier, Martinaud, Hannequin, & Godefroy, 2011;Ritchie, Banks, Danson, Tolson, & Borrowman, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Their support needs differ considerably from those of people with dementia in later years (AM Beattie, Daker-White, Gilliard, & Means, 2002;Sansoni et al, 2016;Sansoni et al, 2014;Thompson, 2011;Tyson, 2007;Westera et al, 2014) as they still have comparatively high levels of physical fitness and are not wellmatched to join more sedentary services designed for older age groups (Pamela Roach, Drummond, & Keady, 2016;Tolhurst, Bhattacharyya, & Kingston, 2014). They also need to negotiate changing family dynamics with a particular focus on children and teenagers (Chow, Pio, & Rockwood, 2011;Gibson, Anderson, & Acocks, 2014;Hutchinson, Roberts, Daly, Bulsara, & Kurrle, 2016;Johannessen, Bruvik, & Hauge, 2015;Lockeridge & Simpson, 2013;Morhardt et al, 2015;P. Roach & Drummond, 2014;Shnall, 2015;Svanberg, Spector, & Stott, 2011;Thompson, 2011), accommodate changing care needs along the disease trajectory (Bakker et al, 2013;Bakker et al, 2010) and need to seek financial and legal advice as employment is discontinued and spouses give up work to become the main caregiver or take on work to compensate for lost income (Alzheimer's Society, 2015;Chaplin & Davidson, 2016;Picard, Pasquier, Martinaud, Hannequin, & Godefroy, 2011;Ritchie, Banks, Danson, Tolson, & Borrowman, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In arguing that a social model of disability can help to empower young people who have a parent living with dementia, Hutchinson et al (2015) call for the 'dementia sector' to embrace technology to establish 'greater connectivity' with young people who have a parent with dementia. Beginning with the recruitment of participants, our study demonstrated the extent to which young people make use of the internet and social media to obtain information and advice and to make contact with others who have had similar experiences and who understand what it is like.…”
Section: Discussionmentioning
confidence: 99%
“…Such an approach has not previously been used in this field. Hutchinson, Roberts, Daly, Bulsara, and Kurrle (2015) have advocated adopting a social model of disability (Oliver, 2009) approach to dementia. They argue this perspective is more likely to empower children and young people who have a parent with dementia because it could better inform the development of more appropriate and inclusionary interdisciplinary services than can follow from the 'traditional' and exclusionary medical model.…”
Section: Methodological Approachmentioning
confidence: 99%
“…Como se identifica, esse conceito está fortemente atrelado à compreensão de empoderamento. A promoção dos meios para que os cidadãos e/ou as comunidades possam ter controle sobre suas próprias vidas e, em consequência, sobre as decisões relevantes a serem tomadas, proporcionando assim autonomia, é definida como empowerment ou empoderamento (12) . Empoderar os cidadãos em relação aos cuidados da sua própria saúde, com base em várias práticas, é desenvolver suas habilidades para o autocuidado.…”
Section: Discussionunclassified